Using an ounce of prevention: does it reduce health care expenditures and reap pounds of profits? A study of the financial impact of wellness and health risk screening programs. - Phillips, Janet F (Journal of health care finance, 2009)
As we are all well aware, health care expenditures in the United States are out of control and growing at epic proportions. Since private industry shoulders a significant burden of paying these rising health care costs, the huge and ever increasing sum paid by these corporations continues to impact the US economy translating into higher prices of services and manufactured goods and reduced job opportunities when companies outsource jobs or locate manufacturing facilities to avoid paying health care benefits for workers. As a result, health care expenditures have become a centerpiece of an enormous public policy debate as Congress is currently working on several versions of a bill to completely revise health care from the ground up. This research project was accomplished to examine the effectiveness of one approach to control rising health care costs and contain corporate financial responsibility–the establishment of wellness and health risk screening programs to improve the health of employees. Total health care cost per insured individual was gathered through an online survey directly from health care benefit administrators. The survey also asked information about wellness and health risk screening programs and the related responses were used to determine if there were a relationship between health care costs and health prevention programs. While statistical analysis was hampered in the current study because of the small sample size, some valid conclusions were reached. The study was successful in identifying a benchmark of Average Total Health Care Cost per Individual from $5,100 to $5,800 for 2005 through 2007. This is especially interesting in light of the fact that an average of $7,026 was spent on health care per person in 2006 in the United States. The study was also able to contribute an estimate of the increase realized in these expenditures of 6 percent in 2007 over 2006, and 4 percent in 2006 over 2005, which were in fact similar to the national average. The final contribution of the study is to suggest an explanation for the costs which appear to be holding their own in terms of the national average. While this cannot be statistically verified, it does seem that the active participation of these companies in wellness programs could be a factor. Wellness programs were very popular in this sample of companies as 82 percent of the respondents answered "YES" when asked if the company funds their own employee wellness program. This is an impressive number of companies that have recognized wellness programs as a potential means to reduce employee health care costs. In regards to specific programs, at least 50 percent of respondents answered that they have smoking cessation, employee fitness, counseling, health risk screening, and bio-metric screening programs. The existence of health screening variables show an impressive 73 percent of respondents do practice some sort of health care screening, 50 percent offer biometric screening while 18 percent have onsite clinics and 23 percent run annual employee fairs.
Place: United States Phillips, Janet F. Southern Connecticut State University, New Haven, CT, USA. Phillipsj1@southernct.edu
Keywords: *Health Care Costs/td [Trends]; *Health Expenditures; *Health Promotion/ec [Economics]; *Occupational Health Services/ec [Economics]; Cost-Benefit Analysis; Health Care Costs; Health Expenditures; Health Promotion; Health risk screening program; Humans; Mass Screening; Mass Screening/ec [Economics]; Occupational Health Services; Preventative health programs; Risk Assessment; Risk Assessment/ec [Economics]; United States; Wellness program; article; biometry; dept.acc; employee; financial management; fitness; funding; government; health care cost; health care financing; health care industry; health care policy; health hazard; occupational health service; patient counseling; preventive health service; profit; responsibility; risk assessment; smoking cessation; wellbeing; ⛔ No DOI found